PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN SDGs DESA UNTUK PENINGKATAN KESEJAHTERAAN TARAF HIDUP TUMBUH MERATA - muhammad sayuti; Hasanuddin Hasanuddin; Syarifuddin Achmad (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2022)
Strengthening the Village SDGs is a government program to provide the value of a prosperous life for today's society, by increasing all potential in achieving goals both in terms of social, economic and environmental comprehensively in the realization of community welfare. Empowerment of management and processing of natural and environmental resource potential which is the community's foundation in cultivating economic resilience for quality and equitable growth which is one of the seven development agendas in the president's vision and mission with the policy direction of the 2020-2024 RPJMN. The implementation of the Village SDGs can be realized if the entire community can play an active role in developing village economic resilience.Therefore, it is necessary to have